INFECTIOUS JUMP SKILLS - Herli Pardilla; Mulyana Mulyana; Achmad Sofyan Hanif (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2018)
The aim of this research is to know the difference of learning method which consists of learning method part (A1), overall method (A2) and combination method (A3) with moderator of motor ability in improving skill. The experiment was conducted by using 2x3 factorial experimental method with population which used as target population. The research was student of Physical Education University of Riau Force 2016/2017 as many as 134 which consist of 89 son and 45 daughter. Sampling was done by selecting 27% of the highest score data and 27% lowest score. Result of hypothesis test 1) difference between group of method part (A1) with group of whole method (A2) equal to t0 (A1 x A2) = -1,699, p-value = 0,096 / 2 = 0,048 <0,05, mean h0 rejected. 2) the difference between the part method group (A1) and the combination method group (A3), worth t0 (A1xA3) = -3.490, p-value = 0.001 / 2 = 0.0005 <0.05, h0 is rejected. 3) the difference between the whole method group (A2) and the combination method group (A3) worth t0 (A2xA3) = -1.791, p-value = 0.080 / 2 = 0.040 <0.05, h0 is rejected. 4) Influence Interaction (Interaction Effect) Fo (AB) = 34,349 with p-value = 0,000 <0,05 or H0 is rejected. This means there is a very significant interaction effect. 5) Differences in skill jump results between high motor and high-motor (A1B1 - A2B1) methods were 3.496, p-value = 0.001 / 2 = 0.0005 <0.05 or H0 rejected. 6) Differences in skill jump results between high motor part and high motor combination method (A1B1 - A3B1) worth = 9.568, p-value = 0,000 / 2 = 0,000 <0.05 or H0 is rejected. 7) Differences in skill jump results between the overall method with high motor and high motor combination method (A2B1 - A3B1) worth = 6,072, p-value = 0.002 / 2 = 0.001 <0.05 or H0 is rejected. 8) The difference in the results of the jump skill between the part method with the low motor and the overall method with low motor (A1B2 - A2B2) worth = 0.286, p-value = 0.680 / 2 = 0.34> 0.05 or H0 is accepted thus, no there are differences.. 9) Differences in skipjack skill results between the low-motor part and low motor combination method (A1B2 - A3B2) = -1,800, p-value = 0.079 / 2 = 0.0395 <0.05 or H0 is rejected .10) Differences in skill jump results between overall and low motor methods and low motorized combination methods (A2B2 - A3B2) = -2.086, p-value = 0.043 / 2 = 0.0215 <0.05 or H0 is rejected. difference. Keywords: infectious jump skills, learning methods and motor skills